PENGARUH RETURN ON ASSET (ROA), LOAN TO DEPOSIT RATIO (LDR), DAN CAPITAL ADEQUANCY RATIO (CAR) TERHADAP HARGA SAHAM PADA PT. BANK NEGARA INDONESIA TBK. - Cicih Ratnasih; Diah Mega Purbayani (Jurnal Manajemen FE-UB, 2018)
This study aims to examine the Effect of Return On Assets (ROA), Loan to Deposit Ratio (LDR) and Capital Adequacy Ratio (CAR) to the Stock Price at PT. Bank Negara Indonesia (Persero) using the method of multiple linear regression analysis. One of the conditions for testing multiple linear regression analysis is to carry out the classical assumption test. This is needed so that the resulting regression equation is BLUE (Best Linear Unbiased Estimator). In addition to assessing the goodness of fit of a model, the coefficient of determination, F test, and t test were tested. This study uses quarterly data from 2004 to 2016 for each research variable.The results of this study indicate that the variables ROA, LDR and CAR have a positive effect on Stock Prices with the value of t-statistic Return on Assets (ROA) of 4.713143 and a probability of 0.0000, Loan to Deposit Ratio (LDR) with t-statistics of 8.636285 and probability amounting to 0.0000, Capital Adequacy Ratio (CAR) with a t-statistic of 2.319119 and a probability of 0.0005. In addition, it was found that the adjusted R-squared value was 0.805576. This means that 80.56% of the stock price index movement can be predicted from the movements of the three independent variables. While the remaining 19.44% is influenced by other variables outside the research. Keywords: Return On Assets, ROA, Loan on Deposit Ratio, LDR, Capital Adequacy Ratio, CAR and Share Prices.